Species‐specific transpiration and water use patterns of two pioneer dominant tree species under manipulated rainfall in a low‐subtropical secondary evergreen forest. Issue 7 (30th June 2020) - Ouyang, Lei; Gao, Jianguo; Zhao, Ping; Rao, Xingquan
Abstract: Like many other ecosystems, subtropical forests are suffering more intense and longer droughts with the ongoing climate change. This study aimed to explore the seasonal transpiration and physiological responses of two dominant tree species, Schima superba and Michelia macclurei, to manipulated precipitation patterns in a subtropical evergreen forest of South China, in which an ambient control treatment (BC), a drier dry and wetter wet season treatment (DD) and an extended dry and wetter wet season treatment (ED) were applied. Tree water use and associated ecophysiological characters, such as the daily whole‐tree transpiration ( E L ), intrinsic water use efficiency ( WUE i ), Huber values ( A s : A l ) and utilization proportions from different water sources were determined during the period from October 2012 to September 2013. For both tree species, no significant difference in transpiration among the three treatments was observed in the wet season, and a relatively stronger decrease of transpiration occurred under DD and ED treatments during the later dry season. Moreover, the higher transpiration of M. macclurei and its advantage of utilizing the shallow water derived from light rainfall under dry condition suggested that it has more survival and growth advantages in this subtropical forest. Therefore, under the seasonal drought caused by uneven distribution of rainfall in the future, M. macclurei that inclines to use shallow soil water would adopt a drought‐avoidance strategy, whereas S. superba that could uptake deeper soil water would be drought tolerant. The different spatial and temporal patterns of water use, together with the contrasting water use strategies, could reduce competition of the two species and facilitate their coexistence under potential precipitation distribution changes.